Contemporary comic books and Hollywood noir: remediating cinematic style and cultural memory in The Fade Out. Issue 3 (4th May 2019) - Diffrient, David Scott
ABSTRACT: This article explores Ed Brubaker and Sean Phillips' recycling of film noir images and tropes in The Fade Out, a twelve-issue comic book series that borrows heavily from photographic and cinematic materials (including publicity stills and actors' head shots) to craft a 'remediated' vision of old Hollywood that is simultaneously deceptive and truthful about the harsh realities of working in an industry popularly known as the 'Dream Factory'. The nightmares that haunt the narrative's protagonist, Charlie Parish, tied to his military past as well as to his relationship to a dead starlet named Valeria Sommers, are referred to by the narrator as 'half-remembered images', a fitting description of the way in which Phillips' own drawings – his nearly 'perfect' reproductions of earlier photos and movie scenes – are actually incomplete without the kind of historical contextualization that this series demands. By juxtaposing panels from the comic book with those original images, the author reveals how, beneath the nostalgic surface of The Fade Out, a deeper message about cultural memory and historical archiving is being articulated. Mixing real-world figures (e.g. screen icons such as Humphrey Bogart, Bette Davis, Clark Gable) and fictional characters who nevertheless call to mind actual people from Hollywood's past, this comic book series invites us to speculate on the demands of the star system as well as on the possibility that our own fading memory might make such distinctions (e.g. between 'real' and 'fake') less clear in the years to come.